The Study on Ergonomic Performances Based on Workstation Design Parameters using Virtual Manufacturing Tool - Iqbal, Mohd; Hasanuddin, Iskandar; Hassan, Azmi; Mohd Soufi, Mohd Syafiq; Erwan, Friesca (International Journal of Integrated Engineering, 2020)
The paper discusses the dimensions of manual workstation in a semi-conductor industry and their effects to the ergonomic performances. The workstation provided quality control activity where the worker need to manually handle thousands of microchips and check their quality. Three dimensions were considered as workstation design parameters, namely as scope distance, scope height and chair height. Three measured were considered as ergonomics performances of the workstation, which were production cycle time, working posture and recommended weight limit. The performances are measured by using Method Time Measurement, Raid Upper Limb Assessment method and NIOSH recommended weight limit method respectively. The study was provided under a virtual manufacturing software. All of the workstation’s components and the activities of the worker are modelled into Delmia V5 (Virtual Ergonomics Solution) software. Design of Experiment (DEO) was conducted by using Design Expert Statistical Software with Central Composite Design of Response Surface Methodology. Fifteen simulation experiments with different dimensions of design parameters were conducted as suggested by the DEO method. The results showed that production cycle time and working posture were affected by all of the design parameters. However, the weight limitation was only affected by scope height and chair height. The study continued to find the dimensions that gave the best ergonomic performance of the workstation.